Danone-Aqua Circular Economy Performance in Maximizing Waste Plastic Value - Cahayani, Ica; Fachurreza, Ahmad Muajaddid; Puspita, Agata Nina (Universitas Negeri Semarang, 2023)
This study discusses the economic performance of the Danone-AQUA circular in maximizing the value of plastic waste in terms of proper plastic waste sorting management or circular packaging, water and carbon circular and business circular. Economy Circular was proposed because of its increasing popularity in the midst of the world's problem with global carbon reduction. The selection of Danone-AQUA Economy Circular is the right way to find out how significant the efforts of non-government organizations are in creating a sustainable economy and environment. This study analyses the performance of Danone-AQUA's circular economy through six circular economy dimensions in managing and maximizing the value of plastic waste in a positive way to reduce the impact of plastic waste workers in Indonesia. This study uses a systematic literature review and adopts a research design to extract research data. The data comes from interviews with Packaging Circularity Senior Manager at Danone, Indonesia. The economic circular performance of Danone-AQUA in maximizing the value of plastic waste contributes to the reduction of plastic bottle packaging waste. The study proves that the impact of circular economy performance in maximizing the value of plastic waste is positive because it increases the function of plastic bottle packaging waste and has value again and reduces the negative impact of plastic waste on the environment. In achieving the performance of maximizing the value of plastic waste, Danone-AQUA applies six circular economy dimensions which are concentrated on three policies, namely packaging circular, water and carbon circular and business circular.